Frequency of germline hereditary non-polyposis colorectal cancer gene mutations in patients with multiple or early onset colorectal adenomas. - Beck, N; Tomlinson, I; Homfray, T; Frayling, I; Hodgson, S; Bodmer, W (1997)
BACKGROUND: The hereditary non-polyposis colorectal cancer (HNPCC) syndrome is caused by germline mutations in mismatch repair genes and predisposes individuals to cancers of the colon and other specific sites. On theoretical grounds, it is expected that patients with HNPCC also develop more colorectal adenomas than the general population. In essence, if the mutation rate is raised owing to mutations at a mismatch repair locus, more mutations are expected at loci such as APC (adenomatous polyposis coli) and more adenomas will start to grow. Not all data support this expectation, however. AIM: To search for germline mutations at HNPCC loci in patients with multiple adenomas. SUBJECTS: Twenty five patients (without known APC mutations) who have developed colorectal adenomas in unusually large numbers and, in some cases, at an early age. METHODS: Germline APC mutations were excluded using the protein truction test for exon 15 and mismatch chemical cleavage analysis for remaining exons. Germline HNPCC mutations were detected by using PCR and single strand conformation polymorphism analysis. RESULTS: Just one germline HNPCC mutation was found (4% of cases) and this was of uncertain functional effect. CONCLUSIONS: In general, germline HNPCC mutations are not responsible for the phenotype of patients with multiple colonic adenomas. It is possible that patients with HNPCC tend to develop adenomas more frequently and earlier than the general population, but that this effect is relatively subtle. These results suggest that individuals with colorectal adenomas only should not strictly be classified as "affected" in HNPCC families (although they should certainly not be classified as "unaffected" either and may warrant intensive screening). In the absence of a personal or strong family history of colorectal cancer, it is probably not worthwhile performing diagnostic or predictive genetic testing for HNPCC mutations in subjects with colorectal adenomas. Although undetected APC mutations may be responsible for some of the phenotypes in this sample, as yet uncharacterised adenoma predisposing genes probably exist.